(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2023)
This article analyses the possibility that some of the most characteristic phonological features of Celtic languages (lenition) may be related to the phonetic values of the consonants of a substratum language akin to Vasconic-Aquitanian in which, hypothetically, the phonological opposition within each articulation point would be based on different degrees of articulatory intensity and not on the degree of sonority (according to a hypothesis defended for Proto-Basque in the past by Martinet, Mitxelena and more recently taken up by Lakarra). This could be explained and could imply a close and very ancient linguistic contact between Pre-Proto-Celtic and Proto-Vasconic, possibly in the southern half of Gaul.